Astragaloside II pretreatment alleviates PM2.5-induced lung injury in mice via MAPK/Nrf2/GPX4 axis-mediated suppression of ferroptosis - Liyun Liu; Zherui Shen; Nan Jia; Qian Chen; Chen Chen; Yi Luo; Xuemei Dai; Sijing Zhao; Caixia Pei; Demei Huang; Yilan Wang; Tao Shen; et al. (Ecotoxicology and Environmental Safety)
Exposure to fine particulate matter (PM2.5) induces inflammation and oxidative stress, contributing to respiratory diseases, including lung injury. Astragaloside II (AS II), a natural product derived from Astragali Radix (AR), demonstrates dual anti-inflammatory and antioxidant activities. This work systematically evaluates AS II's prophylactic efficacy and molecular pathways in mitigating PM2.5-triggered pulmonary damage using a murine model. Intratracheal PM2.5 suspension (7.5 mg/kg) was applied, with AS II (25 and 50 mg/kg) pretreated via intraperitoneal (i.p.) injection before the pollutant challenge. Results demonstrated that AS II alleviated PM2.5-induced lung injury, mitigated pulmonary edema and inflammation, and reduced levels of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). AS II upregulated glutathione (GSH) and catalase (CAT) levels while downregulating reactive oxygen species (ROS) and malondialdehyde (MDA). Mechanistically, AS II inhibited the mitogen-activated protein kinase (MAPK) signalling pathway, activated nuclear factor erythroid 2-related factor 2 (Nrf2), enhanced expression of glutathione peroxidase 4 (GPX4), and elevated other antioxidant proteins while suppressing ferroptosis and oxidative stress markers. To further validate the role of ferroptosis, RSL3—a small-molecule ferroptosis agonist that binds and inactivates GPX4—was employed. The protective efficacy of AS II against lung injury was effectively counteracted by RSL3-induced GPX4 inactivation. Collectively, AS II protects against PM2.5-induced pulmonary injury by modulating the MAPK/NRF2/GPX4 signaling axis to inhibit ferroptosis, thereby providing a novel therapeutic strategy for the treatment of PM2.5-associated pulmonary diseases.